From Cato to the Bronzes of Ticinum: Magical-religious Healing Rituals in Ancient Rome - Marco Simón, Francisco (Acta Classica Universitatis Scientiarum Debreceniensis, 2026)
This paper focuses on two very different rituals in their respective contexts, which provide valuable insights into magical-religious practices in ancient Rome. The first is found in Cato the Elder which contains a series of incantations – characteristic of early Graeco-Egyptian magical papyri, gems and execratory tablets – dating as far back as the early 2nd century BCE. The second ritual is documented on two bronze inscriptions found at Pavia/Ticinum, dating from the 3rd century CE, in which a series of deities are invoked to grant protection to the bearer of these objects. Both pieces of information illustrate the importance of magical-religious healing practices in Roman-Italic societies over a long period.